Comparison of Arterial Blood Gas Analysis versus Central Laboratory Electrolyte and Hemoglobin Determination in Birat Medical College and Teaching Hospital - Arjyal, Batsalya; Rajbanshi, Lalit Kumar; Khanal, Kanak; Bajracharya, Akriti (Birat Journal of Health Sciences, 2020)
Introduction: Electrolyte and hemoglobin measurement are the integral part of management of critically ill patient. There can be a wide variation in the electrolyte and hemoglobin measurement in critically ill patient between arterial blood gas analyzer and central laboratory auto analyzer. Objective: To compare the electrolytes (sodium, potassium and chloride) and hemoglobin level measured by arterial blood gas analyzer and laboratory analyzer. Methodology: This was a prospective cross-sectional comparative study comparing the electrolytes (sodium, potassium and chloride) and hemoglobin measurement between arterial blood gas analyzer and laboratory auto analyzer. The study included 124 paired blood samples from the patient admitted in intensive care unit of Birat Medical College Teaching Hospital in two months duration. The arterial sample and venous sample for electrolytes and hemoglobin measurement were taken simultaneously or not more than one hour apart and analysis was done by arterial blood gas analyzer and central laboratory auto analyzer accordingly. The values of electrolytes and hemoglobin measured by two different analyzers were finally compared for variation. Result: The mean difference calculated for sodium potassium and chloride in ABG machine and Auto-analyzers were 0.57 mmol/l.-0.04mmol/l and 1.71mmol/l respectively. These data were within the acceptable range of United States Clinical Laboratory Improvement Amendments(USCLIA). The mean difference derived for hemoglobin in ABG and Auto-analyzers was 0.16g/dl which was not consistent with the range of United States Clinical Laboratory Improvement Amendments (USCLIA) Conclusion: The measurement of electrolyte namely sodium, potassium and chloride in ABG machines and Auto-analyzers of central lab were comparable while hemoglobin was not comparable under the USCLIA guidelines.